New materials for the light-induced hydrogen evolution reaction from the Cu–Si–Ti–O system. Issue 8 (15th January 2016) - Stein, Helge S.; Gutkowski, Ramona; Siegel, Alexander; Schuhmann, Wolfgang; Ludwig, Alfred
Abstract : Ti:CuSiO3 and Si:Cu3 TiO x are identified as promising photocathode materials with improved stability and high photocurrent densities. Abstract : Cu-containing photocathodes are generally limited by fast photocorrosion under working conditions. Hence stabilization of these materials is a key factor in their potential application for the light-induced hydrogen evolution reaction (HER). In order to identify new materials, oxidized Cu–Si–Ti metallic thin film precursor materials libraries were evaluated using a combinatorial approach. High-throughput photoelectrochemical characterization using an automated optical scanning droplet cell was performed on a material library to analyze doping and alloying effects on the light-induced HER. The results revealed that compositions near Ti-doped CuSiO3 (dioptase and copper-polysilicate) and Si-doped Cu3 TiO x act as comparatively stable and highly active materials for HER.